Voluntary wheel running alters markers of amyloid-beta precursor protein processing in an ovarian hormone depleted model - Mohammad, Ahmad; Finch, Michael S.; Sweezey-Munroe, Jacob; MacPherson, Rebecca E. K. (Frontiers in Endocrinology, 2022)
Aberrant cleavage of the transmembrane protein, amyloid-beta precursor protein (AβPP), results in the overproduction of amyloid-beta (Aβ) peptides which can form senile plaques in the brain. These plaques can get lodged within synapses and disrupt neuronal communication ultimately leading to rampant neuron death. The rate-limiting enzyme in Aβ production is beta-site AβPP cleaving enzyme 1 (BACE1). In females, estrogen loss is associated with increases in Aβ and BACE1 content and activity. Exercise is known to have anti-amyloidogenic effects and may be able to alter BACE1 in cases of ovarian hormone depletion. This study aimed to examine the effects of physical activity on BACE1 in intact and ovariectomized female mice. Female C57BL/6 mice (24 weeks old) underwent bilateral ovariectomy (OVX; n=20) or SHAM surgery (SHAM; n=20). Mice were assigned to one of four groups (n=10/group) for 8 weeks: (1) sham (SHAM), (2) sham with a wheel (SHAM VWR), (3) ovariectomized (OVX), or (4) ovariectomized with a wheel (OVX VWR). Novel object recognition testing demonstrated that OVX mice had a lower percentage of novel object investigation time compared to SHAM. OVX mice also had higher prefrontal cortex BACE1 activity compared to SHAM (p<0.0001), while the OVX+VWR activity was not different from SHAM. Our results demonstrate that voluntary wheel running in an ovariectomized model prevented increases in BACE1 activity, maintained memory recall, and may provide a method of slowing the progression of Alzheimer’s disease.